Knowledge-Based Intelligent Information and Engineering Systems 9th International Conference, KES 2005, Melbourne, Australia, September 14-16, 2005, Proceedings, Part III - Khosla, Rajiv (Lecture Notes in Artificial Intelligence, 2005)
Dear delegates,friendsand membersofthe growingKES professionalcommunity,w- come to the proceedings of the 9th International Conference on Knowledge-Based and IntelligentInformationandEngineeringSystemshostedbyLa TrobeUniversityin M- bourne Australia. The KES conference series has been established for almost a decade, and it cont- ues each year to attract participants from all geographical areas of the world, including Europe, the Americas, Australasia and the Paci?c Rim. The KES conferences cover a wide range of intelligent systems topics. The broad focus of the conference series is the theory and applications of intelligent systems. From a pure research ?eld, intel- gent systems have advanced to the point where their abilities have been incorporated into many business and engineering application areas. KES 2005 provided a valuable mechanism for delegates to obtain an extensive view of the latest research into a range of intelligent-systems algorithms, tools and techniques. The conference also gave de- gates the chance to come into contact with those applying intelligent systems in diverse commercial areas. The combination of theory and practice represented a unique opp- tunity to gain an appreciation of the full spectrum of leading-edge intelligent-systems activity. The papers for KES 2005 were either submitted to invited sessions, chaired and organized by respected experts in their ?elds, or to a general session, managed by an extensive International Program Committee, or to the Intelligent Information Hiding and Multimedia Signal Processing (IIHMSP) Workshop, managed by an International Workshop Technical Committee.